Співвідношення взаємності для відкритих гідродинамічних стаціонарних систем (ВГСС) - Lesnikov, V. P. (Publishing house "Academperiodika", 2019)
Based on Onsager’s regressive hypothesis and a local equilibrium in hydrodynamics, the time symmetry of the mutual correlation functions of fluctuations is analyzed directly from the macroscopic equations of motion for the open steady state of a continuous medium. It is shown that, in OHSS, the flux violates the symmetry of correlation functions and Onsager’s reciprocal relation, which take place near the equilibrium steady state. The reciprocal relations for OHSS are found. Examples of their use are considered.